Perbedaan Efektifitas Konsumai Teh Daun Kelor (Moringa Oleifera) dan Tablet Zat Besi (Fe) Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Putri - Rahmawati A. Sau; Nurain R. Ismail (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Anemia remains a significant nutritional problem among adolescent girls due to increased iron requirements during growth and menstruation. Iron (Fe) tablet supplementation is commonly used for prevention, but low compliance often limits its effectiveness. Moringa oleifera leaf tea offers a potential local food–based alternative intervention. This study aimed to compare the effectiveness of Moringa oleifera leaf tea and iron tablets in increasing hemoglobin levels among anemic adolescent girls. A quasi-experimental two-group pretest–posttest design was employed in December 2025 at two junior high schools in Gorontalo City. The sample consisted of 18 adolescent girls with mild to moderate anemia, divided equally into a Moringa leaf tea group and an iron tablet group. The tea group consumed Moringa leaf tea twice daily for 14 days, while the tablet group consumed one iron tablet per week for two weeks. Hemoglobin levels were measured before and after the intervention using a digital hemoglobin analyzer. Data analysis using the Wilcoxon signed-rank test and Mann–Whitney test showed that both interventions significantly increased hemoglobin levels. However, the increase was greater in the Moringa group (ΔHb 1.4–3.2 g/dL; p = 0.008) compared to the iron tablet group (ΔHb 0.5–0.8 g/dL; p = 0.007). A significant difference between groups (p < 0.001) indicates that Moringa oleifera leaf tea is more effective as an alternative intervention.